Sistem Pendukung Keputusan Penilaian Proposal Kegiatan PNPM MPd Menggunakan Metode Profile Matching dan Analytic Hierarchy Process (AHP) - Mufid, Ahmad (JSINBIS (Jurnal Sistem Informasi Bisnis), 2014)
Assessment of PNPM-MPd’s proposal not run quickly and objectively. The purpose of this research is to create software to help the verification team in conducting an objective assessment of the proposals using the profile matching method and the analytic hierarchy process (AHP). Profile matching method is used to provide an assessment, determination of the gap, and the weighting criteria. While the AHP method is used to calculate the pairwise comparison matrices, eigenvalues​​, priorities, maximum eigenvalues​​, consistency index (CI) and consistency ratio (CR). CR values ​​are used to determine the order in which proposals will be funded by BLM. The final result of this research is decision support system software for assessment of PNPM-MPd’s proposal that can determine the rank of the highest value to lowest. Keywords : Assessment; Profile matching; Analytic Hierarchy Process (AHP)